2011
DOI: 10.3892/or.2010.1096
|View full text |Cite
|
Sign up to set email alerts
|

Fructose transporter Glut5 expression in clear renal cell carcinoma

Abstract: Abstract. Renal cell carcinomas (RCC) can be subclassified for general purposes into clear cell, papillary cell, chromophobe cell carcinomas and oncocytomas. Other tumours such as collecting duct, medullary, mucinous tubular and spindle cell and associated with Xp 11.2 translocations/TFE 3 gene fusion, are much less common. There is also a residual group of unclassified cases. Previous studies have shown that RCC has high glycolytic rates, and expresses GLUT transporters, but no distinction has been made among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 62 publications
2
22
0
Order By: Relevance
“…More recent RNA-seq analyses found human GLUT5 expression in duodenum, bone marrow and kidney [51]. GLUT5 was found to have an association with malignant clear renal cell carcinoma [52]. According to the NCBI Gene database [32,37], orthologs of glut5/slc2a5 are found so far in 123 organisms across chicken, dog, cow, chimpanzee, Rhesus monkey, mouse, rat and X. tropicalis .…”
Section: Glut Transporter Classesmentioning
confidence: 99%
“…More recent RNA-seq analyses found human GLUT5 expression in duodenum, bone marrow and kidney [51]. GLUT5 was found to have an association with malignant clear renal cell carcinoma [52]. According to the NCBI Gene database [32,37], orthologs of glut5/slc2a5 are found so far in 123 organisms across chicken, dog, cow, chimpanzee, Rhesus monkey, mouse, rat and X. tropicalis .…”
Section: Glut Transporter Classesmentioning
confidence: 99%
“…However, the authors did not discuss the survival potential of such a mechanism in cancer cells and did not investigate glycogen accumulation as a general characteristic of tumor cells. Finally, we established that RCC cells, in which pVHL is mutated in approximately 50% of cRCC patients (Kaelin, 2009), showed an enlarged cytoplasm due to abnormalities in glycogen and sterol storage (Medina Villaamil et al, 2011). As tumor cells are addicted to glucose and glucose deprivation occurs in parallel to hypoxia, we hypothesized that the decrease in the oxygen level sensed by cancer cells signals energy storage.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies [40] from our group showed that Glut5 expression associates more strongly with the clear cell RCC subtype. The clear cell subtype of RCC is characterised histologically by a distinctive pale, glassy cytoplasm, and this appearance of clear cell RCC is from abnormalities in the carbohydrate and lipid metabolism; these abnormalities result in glycogen and sterol storage.…”
Section: Discussionmentioning
confidence: 77%